MECHANICAL AND TRIBOLOGICAL PROPERTIES OF POLYMERS AND POLYMER-BASED COMPOSITES - Brostow, Witold; Faltynowicz, Hanna; Gençel, Osman; Grigoriev, Andrei; Lobland, Haley E. Hagg; Zhang, Danny; Gençel, Osman (Lviv Polytech Natl Univ, 2020)
A definition of rigidity of polymers and polymer-based composites (PBCs) by an equation is formulated. We also discuss tribological properties of polymers and PBCs including frictions (static, sliding and rolling) and wear. We discuss connections between viscoelastic recovery in scratch resistance testing with brittleness B, as well as Charpy and Izod impact strengths relations with B. Flexibility Y is related to a dynamic friction. A thermophysical property, namely linear thermal expansivity, is also related to the brittleness B. A discussion of equipment needed to measure a variety of properties is included.
Keywords: Polymer Brittleness; Polymer Flexibility; Polymer Rigidity; Polymer Friction; Polymer Wear; Polymer-Based Composites; Polymer Testing